Economic evaluations of chronic obstructive pulmonary disease pharmacotherapy: how well are the real-world issues of medication adherence, comorbidities and adverse drug-reactions addressed?. (3rd May 2021) - Fens, Tanja; Zhou, Guiling; Postma, Maarten J.; van Puijenbroek, Eugène P.; van Boven, Job F.M.
ABSTRACT: Introduction: When estimating the cost-effectiveness or budget impact of chronic obstructive pulmonary disease (COPD) medication, it is common practice to use trial data for clinical inputs. However, such inputs do not always reflect the real-world situation. Previous reviews recognized the need for taking real-world data (medication adherence, comorbidity and adverse drug reactions [ADRs]) into account. Whether recent cost-effectiveness analyses of COPD medication implemented those recommendations is unknown. Areas covered: The authors reviewed recent economic evaluations of COPD-maintenance treatments focusing on medication adherence, comorbidity and ADRs. Expert opinion: In most registration trials of COPD treatment, strict inclusion and exclusion criteria are applied. During trials, patient monitoring is well controlled. As such, medication adherence is often higher than seen in less controlled, real-world environments with more heterogeneous characteristics. Additionally, safety data collected in trials may not be widely generalizable due to more comorbidity and polypharmacy in the real-world. Consequently, when merely relying on trial data, the impact of adherence, comorbidity and ADRs on the cost-effectiveness can be underestimated. To overcome these real-world data gaps, use of pragmatic trials and observational studies in addition to strictly controlled trial data is recommended. To catalyze implementation of these real-world issues, reporting checklists should be updated.